Likuiditas, Good Corporate Governance, Ukuran Perusahaan, Dan Dampaknya Terhadap Kinerja Perusahaan: Studi pada Perusahaan Manufaktur di BEI periode 2013-2015 - Simon, Suwandi; Kurnia, Ratnawati (Universitas Multimedia Nusantara, 2017)
Financial Statements provides information about financial condition that can be used by stakeholders to analyze firm performance to make the right decisions. The objective of this study was to obtain empirical evidence about the effect of liquidity proxies by Current Ratio, Good Corporate Governance and Firm Size towards Firm Performance proxies by Return on Asset, listed at Indonesia Stock Exchange for the period 2013 2015. Good Corporate Governance proxies by Managerial Ownership, Director Size, Board of Commissioner and Independent Commissioner The object in this research was manufacturing companies listed at Indonesia Stock Exchange (IDX) for the period 2013-2015. The sample was selected by using purposive sampling method. There were 19 companies that fulfill the sample criteria. The secondary data used in this research was analyzed by using multiple regression method. The results of this research were current ratio, managerial owneship, director size, board commissioner, and independent commissioner simultaneously had significant effect towards firm performance. Partially, Director Size and Current Ratio have positive significant effect towards Firm Performance. But Managerial ownership, board of commissioner, and independent commissioner had no positive significant effect towards firm performance. Keywords: Current Ratio, Firm Performance, Firm Size, Good Corporate Governance, Return On Asset I